2011
DOI: 10.3982/ecta9113
|View full text |Cite
|
Sign up to set email alerts
|

Unwilling or Unable to Cheat? Evidence From a Tax Audit Experiment in Denmark

Abstract: This paper analyzes a tax enforcement field experiment in Denmark. In the base year, a stratified and representative sample of over 40,000 individual income tax filers was selected for the experiment. Half of the tax filers were randomly selected to be thoroughly audited, while the rest were deliberately not audited. The following year, threat‐of‐audit letters were randomly assigned and sent to tax filers in both groups. We present three main empirical findings. First, using baseline audit data, we find that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 710 publications
(76 citation statements)
references
References 12 publications
2
60
1
2
Order By: Relevance
“…Moreover, the results suggest that selfemployment decreases the shadow economy. This is at variance with the findings by Kleven et al (2011). Importantly, out of the two indicators (excluding the electricity consumption that is fixed to 1) it is only the economic growth that is statistically significant with the negative sign.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…Moreover, the results suggest that selfemployment decreases the shadow economy. This is at variance with the findings by Kleven et al (2011). Importantly, out of the two indicators (excluding the electricity consumption that is fixed to 1) it is only the economic growth that is statistically significant with the negative sign.…”
Section: Resultscontrasting
confidence: 54%
“…Thus, the positive correlation between the unemployment rate and the size of the shadow econo-my is expected. The choice of using the self-employment rate as a determinant is inspired by a study by Kleven et al (2011) that deals with a higher level of tax evasion for people with a large share of self-reported income. These individuals typically are selfemployed, whereas tax evasion of people with third-party information reporting is virtually nil.…”
Section: Determinants Of the Shadow Economymentioning
confidence: 99%
“…One of them is who reports income. Kleven et al (2011) conducted a large tax enforcement field experiment in Denmark, and showed that tax evasion is near zero for third-party reported income but considerable for self-reported income. This suggests that governments with weak enforcement capabilities may want to 'max out' their use of mechanisms that involve as much self-enforcement as possible.…”
Section: Financial Resourcesmentioning
confidence: 99%
“…Of course, given institutions and tax instruments, tax levels are also relevant for compliance. Kleven et al (2011) showed that higher marginal tax rates lead to more evasion but even more (legal) avoidance. However, in addition to tax levels, the salience of tax penalties and the likelihood of audits may also be relevant.…”
Section: Financial Resourcesmentioning
confidence: 99%
See 1 more Smart Citation